Characteristics of the postural stability of the lower limb in different visual states of undergraduate students with moderate myopia - Huang, Zhaoxin; Xiao, Xiaofei (Frontiers in Physiology, 2023)
Objective: To explore the characteristics of lower limb postural stability in undergraduates with moderate myopia in three different visual states. Methods: Twenty male undergraduate students were recruited to complete respectively the static and dynamic postural stability tests under eyes-closed, myopia (taking off their glasses immediately) and corrected vision conditions. A three-dimensional force platform (Bertec, United States) was used to test static postural stability, which calculated the total path length of the Center of Pressure (COP), path length in the antero-posterior (A/P) and medio-lateral (M/L) directions, COP area, SampleEntropy (SampEn), and low-, medium-, and high-frequency spectrum energies. Dynamic postural stability was tested using the Y-balance test, and the Y-balance test scores were calculated. The Vicon three-dimensional motion capture system (Oxford, United Kingdom) measured the maximum flexion angles of the ankle, knee, and hip joints. The electromyography (EMG) root mean square (RMS) and integral EMG (iEMG) of the tibialis anterior and lateral gastrocnemius of the lower extremity were simultaneously measured using wireless surface electromyography (Noraxon, United States). Results: The SampEn-A/P and SampEn-M/L of corrected vision state higher than myopia and eyes-closed states, and myopia state larger than eyes-closed state (χ² = 51.631, p < 0.001). The original and standard scores of the anterior, postero-medial and comprehensive values of the three visual states had significant differences (F = 32.125, p < 0.001). The original and standard values of postero-lateral corrected vision and myopia were larger than those of eyes-closed states (F = 37.972, p < 0.001). The maximum flexion angles of the ankle and knee joints were in the following order: corrected vision, myopia and eyes-closed (F = 10.93, p < 0.001). The iEMG and RMS had significant differences in the three different states (χ² = 12.700, p < 0.001) in the all directions of YBT. Conclusion: Compared with corrected vision, the stability of static posture in the state of myopia was decreased, and the postural regularity was more regular. The dynamic postural stability in the state of myopia was also lower than that corrected vision, and the activation and work of ankle muscles were also increased.